Film Literacy and Sexual Desires of Female University Student at Pesantren in Madura, Indonesia - Zakiyatul Mufidah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
Film literacy for female university students living in pesantren (santriwati) is a rare issue to discuss since this issue is not considered the primary subject for students living in pesantren (Islamic boarding school). However, it becomes crucial, as the film is a potential media transferring visual ideas about gender and sexuality, which might relate to an individual’s behavior. Moreover, santriwati are likely to have unique characteristics. They are living and learning religiosity in pesantren, and at the same time, they are studying sciences in college or university. Normally, living in pesantren is tied to strict religious norms and traditions. On the other hand, as university students, dealing with a more flexible and open culture is inevitable. They need to read references, watch films, and enjoy novels or other literary works as part of campus life and self-entertainment. This paper examines how film literacy culture among santriwati relates to their sexual desire expression. As many as fifteen santriwati from different pesantren in Madura were taken as the respondents. The results of this study indicate that the literacy culture of film among santriwati affects their expression of sexual desires, although they could hardly express them due to religious norms and values they learned in pesantren.